2015
DOI: 10.1007/s10661-015-4878-7
|View full text |Cite
|
Sign up to set email alerts
|

A reference-based approach for estimating leaf area and cover in the forest herbaceous layer

Abstract: Cover data are used to assess vegetative response to a variety of ecological factors. Estimating cover in the herbaceous layer of forests presents a problem because the communities are structurally complex and rich in species. The currently employed techniques for estimating cover are less than optimal for measuring such rich understories because they are inaccurate, slow, or impracticable. A reference-based approach to estimating cover is presented that compares the area of foliar surfaces to the area of an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The herbaceous layer was sampled in five circular 1 m 2 sub-plots within each of seven circular 0.04 ha permanent sample plots using methods described in Gilliam et al [24]. Briefly, all vascular plants ≤1 m in height in each subplot were identified to species (sometimes to genus) and visually estimated for cover (%); see Walter et al [28] for detailed description of this method. This was carried out in the first week of July each of the sample years 1991,1992,1994,2003, and annually from 2009 to 2014, for a total of 10 sample years over a 24-year period representing 26 years of N treatment on WS3.…”
Section: Field Methodsmentioning
confidence: 99%
“…The herbaceous layer was sampled in five circular 1 m 2 sub-plots within each of seven circular 0.04 ha permanent sample plots using methods described in Gilliam et al [24]. Briefly, all vascular plants ≤1 m in height in each subplot were identified to species (sometimes to genus) and visually estimated for cover (%); see Walter et al [28] for detailed description of this method. This was carried out in the first week of July each of the sample years 1991,1992,1994,2003, and annually from 2009 to 2014, for a total of 10 sample years over a 24-year period representing 26 years of N treatment on WS3.…”
Section: Field Methodsmentioning
confidence: 99%
“…The herbaceous layer was sampled within seven circular 400‐m 2 sample plots in each of WS3 and WS4 (representing the full range of elevation and slope aspect) by identifying and visually estimating cover (%) of all vascular plants ≤1 m in height within five 1‐m 2 circular sub‐plots in each sample plot (Walter et al. ), for a total of 70 1‐m 2 sub‐plots. Sub‐plots were located within sample plots using a stratified‐random polar coordinates method, which was employed to avoid over‐sampling the center region of circular plots (Gaiser ).…”
Section: Methodsmentioning
confidence: 99%
“…We found that visually estimated cover, which does not suffer from these drawbacks, was a good proxy for biomass of individual food species, as well as total graminoid biomass, in complex forest habitats. Such estimation of individual species or portions of the vegetation (in our study area, herbs are more abundant than graminoids) is not feasible with other non-destructive methods (discussed in Radloff and Mucina 2007, Redjadj et al 2012, Walter et al 2015). An objection to the visual estimation of species covers had been that the “sum of species covers” as a measure of total cover would give “non-sense number”s that exceeded 100% (Wilson 2011).…”
Section: Discussionmentioning
confidence: 96%